(untitled) (Journal of Economic Research & Business Administration, 2026)
Managerial activity in small and medium-sized enterprises is carried out under conditions of high uncertainty and instability, which are commonly described in contemporary academic and managerial literature through the VUCA and BANI frameworks. An additional factor complicating managerial activity is digital transformation, including algorithmic decision-support tools, process automation, and increased information load on managers. These conditions significantly complicate managerial decision-making processes and increase the demands placed on managers’ leadership qualities, which are viewed as a key resource for managerial resilience and organizational adaptation to a rapidly changing external environment. At the same time, existing academic research reveals a lack of methodologically robust approaches to the study of leadership qualities that adequately account for uncertainty in the managerial environment and the associated risks of professional burnout. The purpose of this study is to substantiate a methodological approach to the investigation of leadership qualities of small and medium-sized enterprise managers, with a focus on managerial resilience and the prevention of professional burnout under conditions of uncertainty. The article clarifies the theoretical premises underlying leadership research in uncertain environments and formulates the key methodological principles for constructing the proposed research framework. The methodological foundation of the study is based on systemic and interdisciplinary approaches, as well as methods of theoretical analysis, synthesis, and conceptual modeling. The article substantiates the use of a mixed research design that integrates quantitative and qualitative methods, including surveys, semi-structured interviews, and the analysis of managerial experience. The result of the study is the development of a coherent methodological approach that ensures consistency between theoretical analysis, empirical research, and managerial interpretation of data. The scientific contribution of the study lies in refining the methodological foundations for researching leadership under conditions of uncertainty, while its practical significance is associated with the potential application of the findings in the development of managerial development programs, corporate training initiatives, and strategies aimed at preventing professional burnout among managers in small and medium-sized enterprises. Keywords: leadership qualities; methodological approach; managerial resilience; uncertainty; small and medium-sized business.